Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan pada Ditjen Bina Pembangunan Daerah Kementerian Dalam Negeri: The Effect of Compensation and Work Discipline on Employee Performance at the Directorate General of Regional Development of the Ministry of Home Affairs - Raihan Rifai; Frida Apriliafrida.; Sonny Fransisco Siboro (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the effect of compensation and work discipline on employee performance at the Directorate General of Regional Development (Ditjen Bina Bangda) of the Ministry of Home Affairs. The background of this research is based on the importance of human resources as the main factor determining the success of government organizations. Providing fair compensation and implementing consistent work discipline are believed to improve employee performance significantly. This research employs a quantitative method with an associative approach, where data were collected through questionnaires distributed to 50 respondents who are employees of Ditjen Bina Bangda. The analytical techniques used include validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²), processed using SPSS software. The results show that compensation has a positive and significant effect on employee performance, and work discipline also has a positive and significant influence. Simultaneously, both variables contribute strongly to performance improvement, with an R² value of 0.72, meaning that 72% of the variation in employee performance can be explained by compensation and work discipline. These findings indicate that higher compensation and better work discipline lead to higher employee performance. Therefore, it is recommended that the organization continue to strengthen performance-based compensation policies and cultivate a consistent culture of discipline to achieve optimal organizational effectiveness.